Influence of Foam Morphology on Effective Properties Related to Metal Melt Filtration1 . Issue 9 (13th June 2017) - Werzner, Eric; Abendroth, Martin; Demuth, Cornelius; Settgast, Christoph; Trimis, Dimosthenis; Krause, Hartmut; Ray, Subhashis
Abstract : In this article, a numerical study on the sensitivity, related to the performance of open‐cell foams used for the depth filtration of liquid metals, on two characteristic morphological properties is presented. Therefore, simulations of fluid flow and particle transport inside an artificial foam structure are carried out, whose porosity and strut shape is varied within a certain expected range. For comparison purposes, however, the simulations are also performed for three typical ceramic foam filters (CFF) with pore densities of 20 and 30 PPI, whose geometries are obtained from CT scans. In order to allow for a comparison between the different structures, a reference length is introduced that relies upon the actual ratio of pores per volume. The evaluation is mainly based on the comparison of the hydraulic tortuosity, the viscous and the inertial permeability coefficients as well as the initial filtration coefficient for alumina inclusions, with their size ranging from of 10 to 40 μm at process conditions typically encountered during the aluminum filtration. It is shown that the ratio of filtration coefficient and pressure drop increases with the porosity, while the material distribution between the struts and the joints is less influential. Finally, the article also provides information on the anisotropy of CFFs and on the transition behavior from steady to unsteady flow in open‐cell foams. Abstract : This article presents a numerical investigation on the sensitivity of permeability, hydraulic tortuosity, and filtration coefficient of open‐cell foams used for metal melt filtration regarding their porosity and strut shape for conditions typically observed during the continuous casting of aluminum. The predicted results are compared against three samples of real ceramic foam filters obtained through CT scanning.